Exploring Yeh Pulu Relief (An Iconography Approach) - I Wayan Kun Adnyana; I Nengah Sudika Negara; Desi In Diana Sari; A.A Bagus Udayana (Institut Seni Indonesia Denpasar, 2017)
Yeh Pulu relief, located in Bedulu Village, Gianyar Regency, is one of the important Balinese visual art work. It serves as a proof of the ultimate artistic achievement in the ancient Balinese kingdom era. It possesses some distinctive characteristics, such as a particular style of figuration, a specific theme, and unique sculptural characters. There are very few articles focusing on this topic. Therefore, there is a need to explore Yeh Pulu relief by conducting an in-depth research. Based on Panofsky’s iconography perspective, this research aims to analyze stylistic figurations of the relief, the theme, the sculptural characters and the meaning of the depiction. Panofsky’s iconography consists of three levels of analysis, i.e. pre-iconography, iconography and iconology. Employing his theory, the first stage of this analysis focuses on the physical characters on the relief; the second stage focuses on the concept of narration; and the third one deals with discourse around the subject of this study. The image of Yeh Pulu relief very clearly reveals the theme of heroism found in the everyday life by ordinary people. The result of this research is defined of the theme is reinforced by the figuration of the relief’s subjects that tends to be realistic (using the body proportion of a normal adult human) and is complemented by carvings of plant tendrils that are nearly naturalistic in style. The research participants are I Nengah Sudika Negara (data collector), Luh Desi in Diana Sari (layout designer), and Anak Agung Udayana (photographer).Relief Yeh Pulu, lokasi di Desa Bedulu, Kabupaten Gianyar merupakan salah satu karya seni rupa terpenting. Relief ini merupakan pencapaian artistik puncak di era kerajaan Bali Kuna. Selain itu juga memiliki karakter yang khas, seperti gaya figurasi yang khusus, memiliki tema spesifik, dan keunikan pahatan. Sangat sedikit tulisan yang fokus membahas tentang topik ini. Sehingga menjadi penting untuk mengeksplorasi Relief Yeh Pulu melalui riset yang mendalam. Penelitian ini bertujuan untuk menganalisa gaya figurasi, tema, karakter pahatan dan makna dari relief. Melalui pendekatan ikonografi Panofsky, analisis dilakukan melalui tiga tahapan, yakni praikonografi, ikonografi dan ikonologi. Analisis level pertama terfokus pada analisis karakter fisik dari relief; kedua, fokus pada konsep narasi; ketiga, terkait tentang diskursus yang melingkupi subjek kajian. Berdasar analisis tersebut, dapat ditegaskan bahwa relief Yeh Pulu mengungkap tema kepahlawanan dunia sehari-hari orang-orang biasa. Selain itu, dapat disimpulkan pula bahwa secara figurasi relief ini cenderung bersifat realistik (terlihat dari proporsi yang berukuran sama dengan ukuran tubuh manusia dewasa normal), begitu juga dengan pemahatan tentang tetumbuhan yang cenderung bergaya naturalistik. Anggota peneliti di antaranya: I Nengah Sudika Negara (pengumpul data), Luh Desi in Diana Sari (layout desain), dan Anak Agung Udayana (fotografer).